2013
DOI: 10.2144/000114010
|View full text |Cite
|
Sign up to set email alerts
|

A Designed, Phase Changing RTX-Based Peptide for Efficient Bioseparations

Abstract: Typically, chromatography is the most costly and time-consuming step in protein purification. As a result, alternative methods have been sought for bioseparations, including the use of stimulus-responsive tags that can reversibly precipitate out of solution in response to the appropriate stimulus. While effective, stimulus-responsive tags tend to require temperature changes or relatively harsh buffer conditions to induce precipitation. Here we describe a synthetic peptide, based on the natural repeat-in-toxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…The addition of β roll tags to a recombinant protein allows for its selective precipitation in the presence of calcium. The final products presented a high purity and the precipitation protocol only takes a couple of minutes (Shur et al, 2013). Another protein-based stimulus-responsive purification tags are elastin-like polypeptides (ELPs), which consist of tandem repeats of the sequence VPGXG, where X is Val, Ala, or Gly in a 5:2:3 ratio (Meyer and Chilkoti, 1999).…”
Section: Second Question: Which Plasmid Should Be Chosen?mentioning
confidence: 99%
“…The addition of β roll tags to a recombinant protein allows for its selective precipitation in the presence of calcium. The final products presented a high purity and the precipitation protocol only takes a couple of minutes (Shur et al, 2013). Another protein-based stimulus-responsive purification tags are elastin-like polypeptides (ELPs), which consist of tandem repeats of the sequence VPGXG, where X is Val, Ala, or Gly in a 5:2:3 ratio (Meyer and Chilkoti, 1999).…”
Section: Second Question: Which Plasmid Should Be Chosen?mentioning
confidence: 99%
“…A second protein, repeat in toxin (RTX), a calcium‐responsive polypeptide, is also used in a similar fashion. This protein consists of tandem repeated nonapeptide sequences GGXGXDXLX (from five to more than 50 repeats), where X is any amino acid and L can be replaced by I, F, V, or Y occasionally [9, 60]. RTX has been found to switch from a disordered structure to a parallel β;‐roll structure in the presence of calcium ions [60].…”
Section: Purification Tags That Induce Soluble Expression In Vivo Bmentioning
confidence: 99%
“…RTX has been found to switch from a disordered structure to a parallel β;‐roll structure in the presence of calcium ions [60]. Chenal et al identified the universal sequence GGAGNDTLY from a RTX‐containing protein database [9]. This group then devised a purification and separation strategy similar to the one used for Annexin B1 fusion expression, which employs a RTX tag of 153 residues (17 repeats) and an enterokinase (EK) cleavage site.…”
Section: Purification Tags That Induce Soluble Expression In Vivo Bmentioning
confidence: 99%
See 2 more Smart Citations